1970
DOI: 10.1161/01.cir.41.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Cholesterol and Triglyceride Levels by the Combined Administration of Neomycin and Clofibrate

Abstract: The combined oral administration of neomycin (2 g daily) and clofibrate (2 g daily) reduced significantly serum cholesterol levels in 15 of 16 patients. Most of these patients had type II hypercholesterolemia and clinical evidence of arteriosclerosis. The combined regimen of the two drugs was more effective in reducing cholesterol levels in about one third of the patients than administration of either one of these drugs alone. The average decrease of serum cholesterol in these patients while on the combined re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1971
1971
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Samuel, Holtzman, Mailman, and Sekowski have shown that neomycin is an effective agent for treating patients with hypercholesterolemia, especially when used in conjunction with clofibrate (31). The present results lend support to the suggestion that the hypocholesterolemic effect of neomycin is related more to its polybasic molecular structure than to its antibiotic action (32).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Samuel, Holtzman, Mailman, and Sekowski have shown that neomycin is an effective agent for treating patients with hypercholesterolemia, especially when used in conjunction with clofibrate (31). The present results lend support to the suggestion that the hypocholesterolemic effect of neomycin is related more to its polybasic molecular structure than to its antibiotic action (32).…”
Section: Discussionsupporting
confidence: 80%
“…In the control study only 6.6% of the fatty acid was in the precipitate with 43.5% in the micellar phase and 49.9% in the oil phase. The corresponding values for the neomycin study were 34, 31, and 37%, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…He developed coronary artery insuffiency, anginal pain, and electrocardiographic changes at exertion at the age of 12 yr. He was resistant to most serum cholesterol-reducing regimens (14). He was maintained on nitroglycerin and was clinically stable.…”
Section: Methodsmentioning
confidence: 99%
“…It was more potent in reducing triglyceride levels (Moody et al 1984). These findings led to its reclassification as a hypolipidemic agent, similar to clofibrate (Samuel et al 1970). Although Wy14,643 has consistently been highly effective in lowering serum lipid levels, it was never employed clinically because hepatocarcinogenesis was recognized as a side effect of treatment in the early animal studies (Lalwani et al 1981) and was coupled to the lipid lowering actions of Wy14,643 (Reddy et al 1977).…”
Section: P Zahradkamentioning
confidence: 99%